Comparison of mastoid obliteration with middle temporal artery flap versus open cavity: a comparative study - Swami, Himanshu; Arjun, A. P.; Bhat, Sweekritha N. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The objective was to study the outcomes of the canal wall down (CWD) mastoidectomy patients in those with soft canal wall reconstruction by using middle temporal artery (MTA) flap in comparison to those with cavity left open. Methods: A prospective study of 20 patients undergoing CWD surgery was done with 10 in each group of mastoid obliteration and open cavity. The outcomes were studied at 1, 3, 6 and 12 months post-surgery. Results: At the final assessment of 12 months post op, the obliteration group had only 10% patients with grade 1 infection while open cavity group had 40% with grade 2 infection. Obliteration of mastoid cavity and reconstruction of canal wall with soft tissue MTA flap gave excellent control of infection. Conclusions: The MTA flap is highly flexible and versatile for otologic reconstruction with an excellent arc of rotation and robust blood supply. It does not have the issues of resorption, dehiscence or fistula formation faced in other obliteration techniques.